LAW ENFORCEMENT IN ILLEGAL LEVIES BY PUBLIC OFFICIALS ASSOCIATED WITH THE THEORY OF COST AND BENEFIT ANALYSIS - Pratiwi, Miranti Putri (Tadulako Law Review, 2020)
Public officials who carry out illegal levies are threatened with article 12e of Act 31 of 1999 as amended with Act 20 of 2001 concerning Amendments to Act 31 of 1999 concerning Eradication of Corruption. In practice, illegal levies are often carried out in relatively small amounts and are massive. Law enforcement of illegal levies performed by public officials is carried out with the establishment of the Saber Pungli Task Force based on Presidential Regulation (Perpres) 87 of 2016 concerning the Clean-Sweep Illegal Levies Task Force and it will be associated with the theory of Cost and Benefit Analysis. This research uses the normative legal research method by specializing in the approach by using national legal rules to find out law enforcement in cases of illegal levies performed by public officials. The results of this study indicate that law enforcement against illegal levies performed by public officials through the establishment of the Saber Pungli Task Force Team is in line and related to the application of the theory of Cost and Benefit Analysis that compares costs incurred by law enforcement with the benefits obtained through the calculation of losses carried out by illegal levies.